Calculations of the energies of the low‐lying electronic states of dioxatrimethylenemethane (H2CCO2) and prediction of the negative ion photoelectron (NIPE) spectrum of its radical anion†. (23rd June 2016) - Chen, Bo; Hrovat, David A.; Borden, Weston Thatcher; Abe, Manabu; Sheridan, Robert S.
Abstract : In order to predict the energies of the low‐lying electronic states of the dioxa derivative of trimethylenemethane (DOTMM), we have carried out (U)B3LYP, CASPT2, and (U)CCSD(T) calculations, using the aug‐cc‐pVTZ basis set. Our calculations predict that DOTMM has a triplet ground state, with one unpaired electron occupying a b2 σ MO and the other a b1 π MO. An open‐shell singlet state, with the same orbital occupancy as the triplet, is calculated to lie very close to the 3 A2 ground state. However, this open‐shell singlet ( 1 A2 ) is predicted to be the transition structure for methylene rotation and to lead to the barrierless formation of an equivalent pair of α‐lactones. We also report the results of some calculations on thefragmentation of DOTMM to CH2  + CO2 . Our predictions about DOTMM could be tested experimentally by generating the DOTMM − radical anion in the gas phase and obtaining its negative ion photoelectron spectrum. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : Electronic structure calculations have been performed in order to predict the relative energies of the low‐lying electronic states of dioxatrimethylenemethane (DOTMM).